The marvelous adventures of Gus Beezer with Spider-Man - Simone, Gail (The marvelous adventures of Gus Beezer series, 2006)
Gus Beezer, an imaginative kid who eats, sleeps, and breathes Marvel Comics, has a hard time coping at his boring family reunion until he meets a distant cousin with very close ties to Spider-Man.